Decoupling Asia revisited. - Park, Cyn-Young (Metro Manila, Philippines Asian Development Bank, 2017)
First, it examines the progress of regional economic integration which has positively impacted the business cycle comovements both intraregionally and interregionally. Second, with the People Republic of China playing a central role in the regional production network, its ongoing structural changes will likely influence Asia trade patterns and economic integration. Finally, findings from vector autoregression model estimation suggest that the United States economy remains an important source of external demand shock for emerging East Asia, although the impact of the People Republic of China has increased sharply.
Keywords: Asia -- Economic integration; Industry and state; Electronic books